Hubungan Karakteristik dengan Kejadian Hipertensi pada Pasien Rawat Jalan di RSUD Dr. Doris Sylvanus Provinsi Kalimantan Tengah: The Relationship of Characteristics with the Event of Hypertension in Outpatient Patients in RSUD Dr. Doris Sylvanus Central Kalimantan Province - Pebrisiana Pebrisiana; Lensi Natalia Tambunan; Eva Prilelli Baringbing (Jurnal Surya Medika (JSM), 2022)
Hypertension is an increase of systolic blood pressure above the normal value is more than 140 mmHg and diastolic blood pressure of more than 90 mmHg. The characteristics of a person can also affect blood pressure; characteristics of people with hypertension are divided into several: age, gender, education, occupation, and history of hypertension. Hypertension is considered a serious disease because its impact is broad; it can even end in death. This research aims to determine the relationship between the characteristics and prevalence of hypertension. The design of this research is an analytic survey study using a Cross Sectional approach. The sampling method used is Accidental Sampling. The samples taken were 99 respondents; they were outpatients from dr. Doris Sylvanus regional Public Hospital in June-July 2022, this research data was taken using primary data by applying a questionnaire method and then analyzed by univariate and bivariate Furthermore it was tested by using a chi-square test. Research results on age, gender, education, occupation, and history of hypertension that is p-value 0.000 < 0.05 Ha is accepted. This study concludes that there is a relation between characteristics of age, gender, education, occupation, and history of hypertension and the prevalence of hypertension in dr. Doris Sylvanus Regional Public Hospital Central Kalimantan Province in 2022. People are suggested to change their unhealthy lifestyles into healthy ones in purpose avoid the risk of hypertension.